THE EFFECT OF THE POWER OF TWO STRATEGY ON STUDENTS COMPREHENSION OF READING NEWS ITEM TEXT (A STUDY AT THE TWELFTH GRADE OF MAS AL –ABRAAR ANGKOLA SELATAN IN 2020/2021 ACADEMIC YEAR) - ummi khoiriyah tanjung (JURNAL LINER (Language Intelligence and Educational Research), 2021)
The purposes of this research are to find out: 1) The application of The Power of Two Strategy in teaching reading news item text. 2) Students’ reading news item text before and after using the power of two strategy. 3) Whether significant effect of using the power of two strategy at the twelfth grade students of Mas Al-Abraar. Method of the research is experimental. The populations of this research are all the twelfth grade students of Mas Al-Abraar that consist of 45 students. Purposive sample is used to get the sample of the research, the sample consist of 45 students. The techniques of collecting data are observation sheet and test. The result of the application of the power of two strategy is 3.44 categorized ”Very Good”. Before using the power of two 43 categorized “Fail”. Meanwhile, after using the power of two strategy is 79 categorized “good”. The result of ttest 8,95 and ttable 2.02 it means that there is significant effect of using the power of two strategy on students of Mas Al-Abraar in 2020/2021 academic year. Keywords: the power of two strategy , reading. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui: 1) Penerapan Strategi power of two strategy dalam pembelajaran membaca teks item berita. 2) Siswa membaca teks item berita sebelum dan sesudah menggunakan kekuatan power of two strategy. 3) Apakah pengaruh yang signifikan penggunaan kekuatan power of two strategy pada siswa kelas dua belas Mas Al-Abraar. Metode penelitian adalah eksperimental. Populasi penelitian ini adalah seluruh siswa kelas XII Mas Al-Abraar yang berjumlah 45 siswa. Sampel Purposive digunakan untuk mendapatkan sampel penelitian, sampel terdiri dari 45 siswa. Teknik pengumpulan data menggunakan lembar observasi dan tes. Hasil penerapan power of two strategy adalah 3,44 dengan kategori “Sangat Baik”. Sebelum menggunakan power of two strategy 43 dikategorikan "Gagal". Sedangkan setelah menggunakan kekuatan power of two strategy 79 dikategorikan “baik”. Hasil ttest 8,95 dan ttabel 2.02 artinya terdapat pengaruh yang signifikan penggunaan power of two strategy pada mahasiswa Mas Al-Abraar tahun ajaran 2020/2021. kunci: the power of two strategy, reading